2008
DOI: 10.1021/ma801256k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Temperature Response of Branched Poly(N-isopropylacrylamide) Prepared by RAFT Polymerization

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerization in the presence of a compound capable of both reversible chain transfer through a thiocarbonylthio moiety and propagation via a vinyl group led to highly branched copolymers by a method analogous to self-condensing vinyl copolymerization. An acryloyl trithiocarbonate prepared by copper-catalyzed azide-alkyne cycloaddition was copolymerized with N-isopropylacrylamide (NIPAM) in ratios selected to tune the distribution and length of branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 66 publications
3
147
1
Order By: Relevance
“…Trithiocarbonates are known to constitute potent control agents for radical polymerizations of NIPAm [189][190][191][192] (as opposed to, for example, dithiocarbamates). [193] All polymerizations were carried out at atmospheric pressure and 60-70°C in DMF [189] .…”
Section: Experimental Polymerization Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trithiocarbonates are known to constitute potent control agents for radical polymerizations of NIPAm [189][190][191][192] (as opposed to, for example, dithiocarbamates). [193] All polymerizations were carried out at atmospheric pressure and 60-70°C in DMF [189] .…”
Section: Experimental Polymerization Conditionsmentioning
confidence: 99%
“…To then isolate the polymer from the solvent and the extant (solid) monomer, it was first precipitated from the polymerization mixture by addition of diethyl ether, [192,198] which is a solvent for the monomer. The polymer was collected by centrifugation and removal of the supernatant solution.…”
Section: Experimental Polymerization Conditionsmentioning
confidence: 99%
“…Li et al also described the synthesis of PNIPAM-based polymer-protein conjugates with bovine serum albumin (BSA) [37] likewise employing CTA-AZIDE1 as a means of obtaining azido-end-functionalized PNIPAM that was subsequently clicked with a propargyl modified BSA. Vogt et al [36,46] formation of highly branched polymers with the average degree of branching and branch length being readily manipulated via the reaction stoichiometry. Qiu et al [40] reported a route to cyclic PNIPAM from a precursor linear polymer prepared with CTA-AZIDE4 .…”
Section: Reversible Addition-fragmentation Chain Transfer (Raft) and mentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46] As a consequence of the degenerative chain transfer mechanism, (co)polymers prepared by RAFT bear very specific end-groups, the chemical nature of which is dependent on the structure of the chain transfer agent (CTA) and, to a lesser extent, the CTA/initiator pair. Assuming no undesirable side reactions then the a terminus of a (co)polymer chain will be chemically identical to the R-group of the RAFT CTA while the x terminus bears a thiocarbonylthio functional group, the exact chemical structure of which will be dependent of the class of RAFT CTA used, that is, dithioester versus xanthate versus trithiocarbonate etc.…”
Section: Introductionmentioning
confidence: 99%